2011
DOI: 10.4314/wsa.v37i1.64101
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation characterisation and kinetics of m-cresol by <i>Lysinibacillus cresolivorans</i>

Abstract: A novel strain of m-cresol-degrading bacterium, named as Lysinibacillus cresolivorans, was isolated from aerobic sludge from a coking wastewater treatment plant. This bacterium is able to utilise m-cresol as its sole source of carbon and energy. The optimal pH for growth is 6.8 ~ 7.3 and the optimal temperature is 35°C. Compared to organic nitrogen sources, inorganic nitrogen sources were easily utilised for the m-cresol biodegradation. The degradation rate of m-cresol at different starting concentrations was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Both were dominant bacteria in the lake center area but were not detected in the macrophyte‐dominated area, and the genus Lysinibacillus was characterized by extremely high abundance in the lake center area in winter, which may reflect the presence of obligate aerobic bacteria. Related studies have shown that some strains of the genus Lysinibacillus are integral in denitrification, desulfurization, sulfur removal, and biodegradation; can degrade cresols, sulfides, and other pollutants; and are major participants in the treatment of industrial wastewater . The TN and TP contents in the lake center area were low, which may be related to the nitrogen and phosphorus removal characteristics of the genus Lysinibacillus .…”
Section: Discussionmentioning
confidence: 96%
“…Both were dominant bacteria in the lake center area but were not detected in the macrophyte‐dominated area, and the genus Lysinibacillus was characterized by extremely high abundance in the lake center area in winter, which may reflect the presence of obligate aerobic bacteria. Related studies have shown that some strains of the genus Lysinibacillus are integral in denitrification, desulfurization, sulfur removal, and biodegradation; can degrade cresols, sulfides, and other pollutants; and are major participants in the treatment of industrial wastewater . The TN and TP contents in the lake center area were low, which may be related to the nitrogen and phosphorus removal characteristics of the genus Lysinibacillus .…”
Section: Discussionmentioning
confidence: 96%
“…This is an apparent manifestation of the importance of the reactive oxygen species in the organic degradation process. m-cresol has been removed by biological [29][30][31][32][33][34][35] and adsorption [36,37] methods. These methods exhibit good elimination efficiency at low concentrations of m-cresol; however, it is known that the generation of some by-products can be toxic to bacteria, which may reduce their effectiveness.…”
Section: Degradation Of M-cresolmentioning
confidence: 99%
“…Furthermore, they conducted batch experiments at different concentrations of p-cresol and found that the maximum degradation occurs at a concentration of 200 mg/L (Surkatti and El-Naas 2014). Yao et al (2011) identified a novel m-cresol-degrading strain named Lysinibacillus cresolivorans. They investigated the degradation rate of m-cresol at concentrations ranging from 54.1 to 529.1 mg/L.…”
Section: Introductionmentioning
confidence: 99%